Malpractice as a Leading Cause to Maternal Mortality in Egypt: A Postmortem Statistical Study - Sherine S.Ghaleb; Magdy A. Kharoshah; Hisham N.Barakat; Hebat Allah A.Amin; Fadwa A. Elroby (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Maternal deaths are quite common tragic event in developing countries where the main sourceof information on the causes of maternal death is clinical records and autopsies. Knowledge about the causesof these deaths are scarce in Egypt. Efforts to reduce maternal mortality in Egypt are mostly not driven byevidence. This autopsy study was performed to assess the cause of maternal mortality including malpractice,thus providing information which plays an important role in improving clinical practice in Egypt.Methods: A retrospective, descriptive study was conducted at the Egyptian Forensic Authority (EFMA) ina 5-years perios between January 2008 and December 2012 to investigate maternal mortality cases allegedto be due to malpractice.Results:. The total number of maternal deaths was 114 cases. The majority of cases (n=90, 79.0%) werenegative concerning malpractice. Twenty-four deaths (21%) can be attributed to malpractice; 16 due tosurgeon faults and 8 anesthesia-related deaths. The main cause of death was obstetric hemorrhage (n=46)followed by respiratory failure (n=30). Out of the 24 cases, 19 were proved to be due to negligence inthe form of late intervention, improper preparation, unmanaged complication and unauthorized place ofmanagement.Conclusion: Malpractice causes nearly one-fifth of alleged maternal deaths; the most frequenct type ofwhich is negligence. Surgeon errors were double anesthesia related deaths. Hemorrhage was the mostcommon cause of death in malpractice as well as incidental deaths. Quality of obstetric care in Egypt needsfurther improvement in the aspects of health facilities and care providers.